Archaeological Resources of Buton Sultanate as Tourism Assets and Potential Resources for The Religious Harmony In Indonesia - Budi Sulistiono; Anissa Windarti (Badan Riset dan Inovasi Nasional (BRIN), 2026)
The Buton Sultanate has given birth to many glorious past legacies, which we can now see in the form of historical relics, customs, and archaeological resources. The Buton Sultanate has produced several archaeological resources worthy of being fantastic historical tourism destinations, one of which is the Buton Palace Fortress. This study aims to analyze the Buton Sultanate's archaeological resources as tourism assets and potential resources for the religious harmony in Indonesia. This research uses a qualitative descriptive method with an archaeological and historical approach. Data were obtained through focus group discussions, interviews, and observations. Based on the data obtained through historical research and field observations, historical traces of the Buton Sultanate in the Baubau City area and its surroundings still exist as archaeological resources. The Buton Palace Fortress demonstrates the evolution of Buton's socio-cultural system and serves as an educational historical tourist attraction, thus becoming one of Baubau City's tourism assets. These archaeological resources at least show that the Buton Sultanate has given birth to a wealth of history and culture that is very thick with Islamic values ​​in the lives of its people, making Islam the basis of the local culture of the local community.